PENGAKUAN ANAK LUAR KAWIN DALAM PERSPEKTIF HUKUM POSITIF INDONESIA - Ariani, Kurnia Dwi; Silviana, Ana (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to determine the legal factors of judges at the Salatiga District Court in adjudicating applications for recognition of illegitimate children. The research approach used in this study is normative juridical. The data used in this study are secondary data which include primary legal materials, secondary legal materials, and tertiary legal materials. The data obtained are then analyzed qualitatively. The results of this study indicate that the ambiguous provisions regarding the recognition of illegitimate children in Law Number 1 of 1974 concerning Marriage require the resolution of the case through the application of the Civil Code (KUHPerdata) which has not been formally abolished in the Indonesian legal framework as substantive civil law used in the District Court. The legal considerations of the judges at the Salatiga District Court in adjudicating applications for recognition of illegitimate children born before their parents were officially married indicate that the child, Farra Abigail Sherina, is the biological child of the couple Nugroho Fajar Aji and Anissa Alif Putrianti. Furthermore, the applicant's application for recognition of the illegitimate child has met the requirements set out in the Civil Code.